The guide to the CIT-IRP5 panel version 4.0 - Amina Ebrahim; Friedrich Kreuser; Michael Kilumelume (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper presents version 4.0 of the CIT-IRP5 firm-level panel dataset. Version 4.0 is the latest edition of the firm-level component of the combined administrative data using sources from the South African Revenue Service. We show that differences in forms and vintages do generally not preclude consistent identification of output, employment, cost of sales, and capital stock over time. We discuss the inclusion of contributions by other researchers in the classification of multi-national firms, industry, and employment income. The tax dataset is shown to have within-firm consistency with previous versions of the data, and the improvements to the data result in greater consistency with external data sources.
Keywords: C55; C80; 330; administrative data; tax; firm-level